The Pro Tools 2023 Post-Audio Cookbook : a holistic approach to post audio workflows like music production, motion picture, and spoken word - Paternostro, Emiliano (Packt Publishing Ltd., 2023)
Take your projects from vision to victory with Avid Pro Tools by delivering high-quality results with perfect recipes for every challenge Purchase of the print or Kindle book includes a free PDF eBook Key Features Learn to edit audio quickly and efficiently using different techniques Discover advanced automation techniques used during a mix session Unlock Pro Tools' most powerful features and explore their uses Book Description Pro Tools has long been an industry-standard Digital Audio Workstation (DAW) for audio professionals, but it can often be overwhelming for new and experienced users alike. The Pro Tools 2023 Post-Audio Cookbook acts as a reference guide to the software and breaks down each stage of a project into manageable phases. From planning a session, editing a sequence, performing a mix to printing the final masters, you can approach this book either sequentially or peruse the self-contained recipes. You'll come to grips with workflows for music production, motion picture, and spoken word production, helping you gain expertise in the area of your choice. You'll learn aspects of music mixing like side chain processing to keep instruments from overshadowing each other and conforming for motion picture. The author's expertise with Pro Tools will help you discover and incorporate different techniques into your workflows. You'll also learn to build consistent and replicable workflows and templates by understanding what happens behind the scenes in Pro Tools. With this cookbook, you'll be able to focus on the creative aspects of your audio production and not get mired by the technical hurdles. By the end of this book, you'll be well-equipped to handle even the most complex features of Pro Tools to deliver immaculate results for your clients. What you will learn Explore the inner workings of Pro Tools Plan and organize projects effectively Edit audio quickly and efficiently Understand and explore the usage of audio routing Build effective mix templates Deliver custom solutions for varied service requirements Use advanced mixing techniques to enhance sound tracks Pick appropriate use cases for different audio effects and plugins Who this book is for The book is for audio professionals, sound designers/editors, music engineers, podcast producers, re-recordist mixers, and students looking to learn about Pro Tools and its features. A basic understanding of Digital Audio Workstations and its operations such as import, edit, mix and bounce is a must.